Exercise-induced vascular remodeling - Prior, B. M.; Lloyd, P. G.; Yang, H. T. (Exercise and Sport Sciences Reviews, 2003)
Exercise produces a powerful angiogenic stimulus within the active muscle that leads to a functionally important increase in capillarity. Further, exercise can increase flow capacity by enlarging the caliber of arterial supply vessels. These adaptations are achieved by the processes of angiogenesis and arteriogenesis, respectively.